Appropriate Timing of Coronary Artery Bypass Graft Surgery for Acute Myocardial Infarction Patients: A Meta-Analysis - Lang, Qianlei; Qin, Chaoyi; Meng, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Currently, percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) are commonly used in the treatment of coronary atherosclerotic heart disease. But the optimal timing for coronary artery bypass grafting after acute myocardial infarction (AMI) is still controversial. The purpose of this article was to evaluate the optimal timing for CABG in AMI). Methods: We searched the PubMed, Embase and Cochrane library databases for documents that met the requirements. The primary outcome was the in-hospital mortality. The secondary outcomes were perioperative MI incidence and cerebrovascular accident incidence. Results: The search strategy produced 1,742 studies, of which 19 studies (including data from 113,984 participants) were included in our analysis. The OR of in-hospital mortality between early 24 h CABG and late 24 h CABG group was 2.65 (95%CI: 1.96 to 3.58; P＜0.00001). In both STEMI and undefined STEMI/NSTEMI subgroup, the mortality in the early 24 h CABG group (OR: 2.62; 95% CI: 1.58 to 4.35; P＝0.0002. vs. OR: 3.88; 95%CI: 2.69 to 5.60; P＜0.00001) was significantly higher than the late 24 h CABG group. However, the mortality of early 24 h CABG group (OR: 1.24; 95%CI: 0.83 to 1.85; P=0.29) was not significantly different from that of late 24 h CABG group in NSTEMI group. The OR of in-hospital mortality between early 48 h CABG and late 48 h CABG group was 1.91 (95%CI: 1.11 to 3.29; P＝0.02). In the undefined STEMI/NSTEMI subgroup, the mortality in the early 48 h CABG group (OR: 2.84; 95%CI: 1.31 to 6.14; P＜0.00001) was higher than the late 48 h CABG group. The OR of perioperative MI and cerebrovascular accident between early CABG and late CABG group were 1.38 (95%CI: 0.41 to 4.72; P=0.60) and 1.31 (95%CI: 0.72 to 2.39; P=0.38), respectively. Conclusions: The risk of early CABG could be higher in STEMI patients, and CABG should be delayed until 24 h later as far as possible. However, the timing of CABG does not affect mortality in NSTEMI patients. There was no statistical difference in perioperative MI and cerebrovascular accident between early and late CABG.